UPROOTING A CULTURE OF GENDER-BASED VIOLENCE IN SOUTH AFRICA: CRITICAL APPROACHES TO BAIL, POLICING AND AWARENESS - Nortje, Windell; Hull, Shane (Obiter, 2024)
Gender-based violence (GBV) is a serious and systemic problem in South Africa. The government has attempted to address the problem by introducing several initiatives including sexual offences courts, and various laws aimed at protecting women and children. However, the recent reform is not sufficient. Only a limited number of bail reforms were introduced. This article proposes several additional bail reforms aimed at protecting women and children against GBV. Also, more proactive measures need to be undertaken to reduce GBV. This includes reform in the South African Police Service (SAPS) and awareness campaigns. These initiatives are important because they target GBV at its roots. First, the article provides a brief overview of the culture of GBV and the efforts of the South African government to curb it. This is followed by an analysis of how bail proceedings can be amended to have a greater impact on GBV prevention. The article then analyses proactive measures geared towards improving the role of the SAPS, and promoting awareness campaigns to combat the scourge of GBV.